1982
DOI: 10.1002/ccd.1810080408
|View full text |Cite
|
Sign up to set email alerts
|

The role of coronary thrombosis in myocardial infarction: Further evidence shown by intracoronary thrombolysis with streptokinase

Abstract: Myocardial infarction is usually caused by a thrombus occurring on a significant coronary lesion. A 60-year-old male was admitted with an acute evolving anterior myocardial infarction. Three hours after the beginning of chest pain, the electrocardiogram showed ST-segment elevation in the anterior and lateral leads which persisted despite intravenous nitroglycerin (100 mcg/min). One hour later, an angiogram showed complete obstruction at the origin of the left anterior descending artery (LAD). After intracorona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1983
1983
1984
1984

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Gagnon et al [9] reported a case of intracoronary thrombolysis without significant narrowing in the chronic stage and suggested that an occlusive thrombus, arising on the very mild atheromatous change, was completely resolved in the hospital course. Although the case herein reported is somewhat like that of Gagnon et al, the resolving thrombus was directly shown in the angiogram in the acute stage (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Gagnon et al [9] reported a case of intracoronary thrombolysis without significant narrowing in the chronic stage and suggested that an occlusive thrombus, arising on the very mild atheromatous change, was completely resolved in the hospital course. Although the case herein reported is somewhat like that of Gagnon et al, the resolving thrombus was directly shown in the angiogram in the acute stage (Fig.…”
Section: Discussionmentioning
confidence: 97%